INVESTIGATING EFL STUDENTS’ AUTONOMOUS LEARNING IN READING ACTIVITY DURING ONLINE LEARNING - Vivi Nur Imami Anggraini (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study was aimed at finding out how EFL students’ reading activities during online learning and the factors influence their reading activity. In this study, the researcher used qualitative approach with descriptive qualitative design The subject of this study are five English Education Department students of University Islam Malang. The findings showed some students’ reading activities, such as  reading English article and e-book, reading through application, reading English novel, and reading through social media. Keywords: Reading Skill, Reading Activity, Autonomous Learning, Online Learning